Comparison of Conjunctival Autograft and Intra-Operative Application of Mitomycin-C in Treatment of Primary Pterygium - Fawad Rizvi, Zeeshan Kamil, Syeda Aisha Bokhari (Pakistan Journal of Ophthalmology, 2011)
Purpose: The purpose of this study was to evaluate and compare recurrence rate in treating primary pterygium by two different techniques: pterygium excision with intra-operative application of mitomycin C versus pterygium excision and conjunctival autograft. Material and Methods: The patients were selected from the out-patient department of L.R.B.T Free Base Eye Hospital, Karachi from 1st December 2009 to 30th November 2010. Eighty patients with primary pterygium were included in this study with age ranging between 20-50 years. Patients were randomly allocated into two groups: Group A consisted of 40 patients who were operated on for pterygium excision and conjunctival autograft. Group B consisted of 40 patients who were operated for pterygium excision and intra-operative application of mitomycin C (0.02%). Complications and recurrences were assessed and compared. Results: In Group A, there were 2 (5%) recurrences noted with minor complications in 6 (15%) of the cases. In Group B, there were 9 (22.5%) recurrences noted along with minor complications in 10 (25%) of the cases. Conclusion: Pterygium excision with conjunctival autograft is a superior technique in terms of lower rates of recurrences and complications as compared to pterygium excision with intra-operative use of mitomycin C.